Effect of ajmaline on transient outward current in rat ventricular myocytes - Bébarová, M; Matejovic, P; Pásek, M; Simurdová, M; Simurda, J (General physiology and biophysics, 2005)
The mechanism of ajmaline-induced inhibition of the transient outward current (I(to)) has been investigated in right ventricular myocytes of rat using the whole cell patch clamp technique. Ajmaline decreased the amplitude and the time integral of I(to) in a concentration-dependent, but frequency- and use-independent manner. In contrast to the single exponential time course of I(to)-inactivation in control conditions (tau(i) = 37.1 +/- 2.7 ms), the apparent inactivation was fitted by a sum of two exponentials under the effect of ajmaline with concentration-dependent fast and slow components (tau(f) = 11.7 +/- 0.8 ms, tau(s) = 57.6 +/- 2.7 ms at 10 micromol/l) suggesting block development primarily in the open channel state. An improved expression enabling to calculate the association and dissociation rate constants from the concentration dependence of tau(f) and tau(s) was derived and resulted in k(on) = 4.57 x 10(6) +/- 0.32 x 10(6) mol(-1).l.s(-1) and k(off) = 20.12 +/- 5.99 s(-1). The value of K(d) = 4.4 micromol/l calculated as k(off) / k(on) was considerably lower than IC(50) = 25.9 +/- 2.9 micromol/l evaluated from the concentration dependence of the integrals of I(to). Simulations on a simple model combining Hodgkin-Huxley type gating kinetics and drug-channel interaction entirely in open channel state agreed well with the experimental data including the difference between the K(d) and IC(50). According to the model, the fraction of blocked channels increases upon depolarization and declines if depolarization is prolonged. The repolarizing step induces recovery from block with time constant of 52 ms. We conclude that in the rat right ventricular myocytes, ajmaline is an open channel blocker with fast recovery from the block at resting voltage.
Keywords: Ion Channel Gating; Membrane Potentials; srdeční komory; draslíkové kanály; Male; Rats, Wistar; Electric Conductivity; Computer Simulation; gating iontového kanálu; ajmalin; vztah mezi dávkou a účinkem léčiva; mužské pohlaví; potkani Wistar; Models, Biological; membránové potenciály; elektrická vodivost; krysa rodu Rattus; kultivované buňky; Potassium Channels; kardiomyocyty; Animals; biologické modely; zvířata; Anti-Arrhythmia Agents; Rats; Myocytes, Cardiac; počítačová simulace; Cells, Cultured; Heart Ventricles; Dose-Response Relationship, Drug; antiarytmika; Ajmaline